2013
DOI: 10.1371/journal.pone.0065807
|View full text |Cite
|
Sign up to set email alerts
|

Species Differences in the Immunoreactive Expression of Oxytocin, Vasopressin, Tyrosine Hydroxylase and Estrogen Receptor Alpha in the Brain of Mongolian Gerbils (Meriones unguiculatus) and Chinese Striped Hamsters (Cricetulus barabensis)

Abstract: Species differences in neurochemical expression and activity in the brain may play an important role in species-specific patterns of social behavior. In the present study, we used immunoreactive (ir) labeling to compare the regional density of cells containing oxytocin (OT), vasopressin (AVP), tyrosine hydroxylase (TH), or estrogen receptor alpha (ERα) staining in the brains of social Mongolian gerbils (Meriones unguiculatus) and solitary Chinese striped hamsters (Cricetulus barabensis). Multiple region- and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 118 publications
(109 reference statements)
1
13
0
Order By: Relevance
“…Sex differences in VP neurons and plasma VP concentrations have also been found in humans (Share et al, 1988; Asplund & Aberg, 1991; Van Londen et al, 1997; Ishinina et al, 1999; Miller et al, 2013; Graugaard-Jensen et al, 2014; however, see Fliers et al, 1985; Swaab et al, 2001; Gouin et al, 2012). In contrast, we found that only a few rodent species show sex differences in OT-immunoreactivity (CD mice: Häussler et al, 1990; mandarin voles: Qiao et al, 2014; Brandt’s voles: Xu et al, 2010; Mongolian gerbils and Chinese-striped hamsters: Wang et al, 2013). There is also a lack of sex differences in OT neuron size and number in humans (Fliers et al, 1985; Wierda et al, 1991; Ishunina and Swaab, 1999), and most human studies report a lack of sex differences in plasma OT (Zhong et al, 2012; Taylor et al, 2010; Grewen et al, 2005; Gordon et al, 2008; Gordon et al, 2010; Graugaard-Jensen et al, 2014; however see van Londen et al, 1997; Miller et al, 2013; Weisman et al, 2013).…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…Sex differences in VP neurons and plasma VP concentrations have also been found in humans (Share et al, 1988; Asplund & Aberg, 1991; Van Londen et al, 1997; Ishinina et al, 1999; Miller et al, 2013; Graugaard-Jensen et al, 2014; however, see Fliers et al, 1985; Swaab et al, 2001; Gouin et al, 2012). In contrast, we found that only a few rodent species show sex differences in OT-immunoreactivity (CD mice: Häussler et al, 1990; mandarin voles: Qiao et al, 2014; Brandt’s voles: Xu et al, 2010; Mongolian gerbils and Chinese-striped hamsters: Wang et al, 2013). There is also a lack of sex differences in OT neuron size and number in humans (Fliers et al, 1985; Wierda et al, 1991; Ishunina and Swaab, 1999), and most human studies report a lack of sex differences in plasma OT (Zhong et al, 2012; Taylor et al, 2010; Grewen et al, 2005; Gordon et al, 2008; Gordon et al, 2010; Graugaard-Jensen et al, 2014; however see van Londen et al, 1997; Miller et al, 2013; Weisman et al, 2013).…”
Section: Discussionmentioning
confidence: 57%
“…In detail, VP synthesis in hypothalamic regions is similar between male and female mice (PVN and SON: Joca et al, 2013; Steinman et al, 2015), voles (PVN, SON, SCN in prairie, pine, meadow, and montane voles: Wang, 1995; Wang et al, 1996), Mongolian gerbils (PVN, medial preoptic area [MPOA], lateral hypothalamus [LH] and anterior hypothalamus [AH]: Wang et al, 2013), and Chinese striped hamsters (PVN, medial preoptic area, lateral hypothalamus and anterior hypothalamus: Wang et al, 2013). However, other rodent species show region- and social context-specific sex differences in hypothalamic VP-immunoreactivity.…”
Section: Sex Differences In Vasopressin and Oxytocin Synthesis Andmentioning
confidence: 99%
See 3 more Smart Citations